2020
DOI: 10.1159/000509657
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumour DNA to Guide Treatment of Gastrointestinal Malignancies

Abstract: <b><i>Background:</i></b> Gastrointestinal cancers are among the most common cancers worldwide and account for a high proportion of cancer-related mortality. Advancements to improve outcomes are constrained by the lack of biomarkers that can offer early diagnostic and prognostic information as traditional serological tumour markers and conventional imaging approaches are not able to provide early information regarding disease recurrence and treatment outcomes. Recent advances in technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Liquid biopsy could provide essential benefits for adjuvant and palliative treatment decision making, but low detection rates in nonmetastatic UGI cancers hinders this. Positive ctDNA after neoadjuvant treatment can identify patients with significantly increased risk of relapse (HR: 18.7), distant metastases (HR: 32.1), and cancer-associated death (HR: 23.1), but identifying how this issue should be addressed for significant survival benefit is a key question for further studies[ 7 ]. Moreover, liquid biopsy may become integrated into treatment response prediction, especially of immunotherapy, in advanced UGI cancers[ 83 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Liquid biopsy could provide essential benefits for adjuvant and palliative treatment decision making, but low detection rates in nonmetastatic UGI cancers hinders this. Positive ctDNA after neoadjuvant treatment can identify patients with significantly increased risk of relapse (HR: 18.7), distant metastases (HR: 32.1), and cancer-associated death (HR: 23.1), but identifying how this issue should be addressed for significant survival benefit is a key question for further studies[ 7 ]. Moreover, liquid biopsy may become integrated into treatment response prediction, especially of immunotherapy, in advanced UGI cancers[ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, detection rates of UGI cancers are low in the early stages (approximately 20%) and reporting studies, thus, have low case numbers[ 19 ]. However, potential targets for molecular tracking are: HOXD10 (higher methylation rates in more advanced disease); ZIC1, RUNX3, and TP53 (53%); or receptor tyrosine kinases, including KRAS (15%), FGFR2, EGFR (17%), ERBB2, PIK3CA (13%), or HER2 (17%)[ 7 , 20 , 21 ]. NGS of metastatic UGI cancer in small case studies revealed detection rates of up to 87.5%[ 21 ].…”
Section: Upper Gi Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…One of the commonest platforms used is the polymerase chain reaction (PCR)-based assays, which include droplet digital PCR (ddPCR), quantitative real-time (RT-qPCR) and ‘Beads, Emulsion, Amplification and Magnetics’ (BEAMing) PCR ( 8 , 9 ). Another type of platform is to apply Next-Generation Sequencing (NGS) on a target panel of genomic alterations, examples of which include the Tagged-Amplicon deep sequencing (TAm-seq), Safe-sequencing System (Safe-SeqS) and CAncer Personalized Profiling by deep sequencing (CAPP-Seq) ( 8 , 10 ). Such NGS-based assays are highly sensitive with a Limit of Detection (LOD) of variant allelic frequencies (VAF) as low as 0.01%, and specific in detecting various mutations including indels, rearrangements and copy number alterations (CNAs) in GI cancers.…”
Section: Overview Of Ctdna As a Biomarker In Gastrointestinal Cancersmentioning
confidence: 99%